Flow cytometric DNA analysis in longstanding ulcerative colitis: a method of prediction of dysplasia and carcinoma development?. Issue 9 (September 1987) - Löfberg, R; Tribukait, B; Ost, A; Broström, O; Reichard, H
Abstract : During a prospective study lasting 3.5 years flow cytometric DNA analysis was evaluated as a possible predictor of dysplastic and malignant lesions in longstanding ulcerative colitis. Fifty three patients with total ulcerative colitis (mean disease duration of 22 years) were regularly colonoscoped. Biopsies of colonic mucosa were analysed by flow cytometric technique and were also assessed histologically. Findings of abnormal DNA pattern (aneuploidy) were compared with findings of dysplasia. Five patients (9%) had aneuploidy, four of those at repeated colonoscopies. Four of those patients also had various degrees of dysplasia. In one patient aneuploidy preceded the finding of dysplasia and in another aneuploidy preceded a well differentiated adenocarcinoma, grade Dukes' A subsequently found at surgery. Four additional patients had dysplasia, all in connection with macroscopic lesions, but were diploid. It is suggested that flow cytometric DNA analysis in long standing ulcerative colitis may be helpful in addition to histopathology in the detection of potential malignancy in ulcerative colitis.